Upaya Peningkatan Hasil Belajar Siswa Dengan Menggunakan Model Pembelajaran Kooperatif Tipe (Nht) Pada Materi Ruang Dimensi Tiga - Nurlaila H. Tasanif (Peneliti.net, 2022)
This Classroom Action Research (PTK) is entitled Efforts to Improve Student Learning Outcomes Using the Numbered Heads Together (NHT) cooperative learning model to improve student mathematics learning outcomes in Three Dimensional Space material. The problem in this study is whether the Numbered Heads Together (NHT) cooperative learning method can improve student learning outcomes in mathematics. The data collection technique used was student observation sheets and written test results. The results showed that the cooperative learning method of the Numbered Heads Together (NHT) type could improve the mathematical thinking abilities of class X students of MA Muhammadiyah Pabos for the 2021 academic year in cycle I, the presentation of student activity was 56% and the presentation of classical completeness was 56%, and in cycle II, experiencing an increase in activity by 81% with classical mastery of 81%. The results showed that the Numbered Heads Together (NHT) type of cooperative learning model could improve the learning outcomes of class X MA Muhammadiyah Pabos students on material Three Dimensional Space 2021 in cycle I the average value obtained students are still lacking, namely 74% With the classical provisions of 75%, in cycle II the average student score increased to 80.56 with the classical provisions of 81%.